The Implementation Of Kitab Mau'izhatul Mukminin From Ihya' Ulumuddin In The Character Building Of Students At Madrasah Al-Qismul 'Aly Al-Washliyah Batubara - Khadafi, Muammar; Agustia, Nanda Rahayu (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research examines the book Mau'izhatul Mukminin Min Ihya' Ulumuddin which is one of the mandatory learning at Madrasah Al-Qismul 'Aly Al-Washliyah Batubara. This research shows students' understanding in understanding and practicing the teachings of the book. This research aims to examine the learning of the book of Mau'izhatul Mukminin Min Ihya' Ulumuddin in the development of student morals at Madrasah Al-Qismul 'Aly Al-Washliyah Batubara. This study uses a qualitative method, with a phenomenological research type. Data collection techniques through in-depth interviews, observation and documentation. The data analysis technique uses phenomenological techniques. The findings or results of the research include: (1) In-depth discussion, The subject of the research is that the teacher has a deep understanding of the moral values in the book. (2) The growth of morals includes: Students bow their heads when passing in front of the teacher, respect and ta'zhim to the teacher, shake hands with friends when meeting and provide the teacher with drinking water before the teacher starts learning. (3) Obedience to Allah, the implementation of the Book of Mau'izhatul Mukminin Min Ihya' Ulumuddin has a significant impact on students' obedience to Allah. (4) The influence of teacher exemplary, This finding also includes how teachers can influence education and moral development in students.